2016
DOI: 10.1111/evo.13143
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and competitors suppress bacterial pathogen synergistically due to evolutionary trade-offs

Abstract: Parasites and competitors are important for regulating pathogen densities and subsequent disease dynamics. It is, however, unclear to what extent this is driven by ecological and evolutionary processes. Here, we used experimental evolution to study the eco‐evolutionary feedbacks among Ralstonia solanacearum bacterial pathogen, Ralstonia‐specific phage parasite, and Bacillus amyloliquefaciens competitor bacterium in the laboratory and plant rhizosphere. We found that while the phage had a small effect on pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 52 publications
(142 reference statements)
4
54
0
1
Order By: Relevance
“…PAS is thought to occur because two sufficiently different selective pressures are more likely to kill both nonresistant (susceptible to antibiotics) and antibiotic‐resistant (susceptible to phages) pathogen genotypes (Torres‐Barceló & Hochberg, 2016). Moreover, two concurrently acting selection pressures might impose evolutionary trade‐offs for the pathogen, which could constrain the evolution of resistance to antibiotics, phage or both (Chan et al., 2016; Torres‐Barceló & Hochberg, 2016; Wang et al., 2017). Here, we studied this using a model system where we exposed P. aeruginosa pathogen to both phage and sublethal concentration of gentamycin and monitored ecological and evolutionary dynamics in both homogenous (planktonic) and spatial (biofilm) dimensions of the microcosms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAS is thought to occur because two sufficiently different selective pressures are more likely to kill both nonresistant (susceptible to antibiotics) and antibiotic‐resistant (susceptible to phages) pathogen genotypes (Torres‐Barceló & Hochberg, 2016). Moreover, two concurrently acting selection pressures might impose evolutionary trade‐offs for the pathogen, which could constrain the evolution of resistance to antibiotics, phage or both (Chan et al., 2016; Torres‐Barceló & Hochberg, 2016; Wang et al., 2017). Here, we studied this using a model system where we exposed P. aeruginosa pathogen to both phage and sublethal concentration of gentamycin and monitored ecological and evolutionary dynamics in both homogenous (planktonic) and spatial (biofilm) dimensions of the microcosms.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations that change the structure of these receptors has been shown to confer P. aeruginosa resistance to phages, but at the same time increase its susceptibility to antibiotics due to its less functional efflux pump (Chan et al., 2016). In the same way, it has recently been reported that phage selection can make Ralstonia solanacearum plant pathogenic bacterium more susceptible to antibiotics produced by Bacillus amyloliquefaciens biocontrol bacterium even though the mechanism has not yet been described in detail (Wang et al., 2017). Third, selection by phages and antibiotics could lead to increased costs of resistance, which could limit bacterial growth and infectiveness (Andersson & Hughes, 2010; Friman et al., 2016; Mumford & Friman, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Meaden and Koskella ; Wang et al. ; De Sordi et al. ), and none have directly compared the outcome of serially passaged bacteria and phage in vitro and in vivo .…”
mentioning
confidence: 99%
“…Wang et al. () propose that this pattern could be explained by an evolutionary trade‐off where the combination of the phage and B. amyloliquefaciens reduces population densities of R. solanacearum more than either antagonist individually. This trade‐off occurs because phage‐treated R. solanacearum populations become more susceptible to antimicrobial metabolites produced by B. amyloliquefaciens .…”
mentioning
confidence: 99%